2009
DOI: 10.1590/s1807-59322009000700008
|View full text |Cite
|
Sign up to set email alerts
|

Within-Breath Analysis of Respiratory Mechanics in Asthmatic Patients by Forced Oscillation

Abstract: INTRODUCTION:The within-breath analysis of respiratory mechanics by the monofrequency Forced Oscillation Technique (mFOT) is of great interest in both physiopathology studies and the diagnosis of respiratory diseases. However, there are limited data on the use of this technique in the analysis of asthma. This study evaluates within-breath mechanics of asthmatic individuals and the contribution of the mFOT in the asthma diagnosis.METHODS:Twenty-two healthy and twenty-two asthmatic subjects, including patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
5
16
0
Order By: Relevance
“…Under these conditions, Ze was the most suitable for correctly identifying the effects of COPD, with a sensitivity of 100% and a specificity of 90%. These promising results are consistent with those obtained previously21,44 and suggest that the Zrs observed in different phases of the respiratory cycle may be useful in the detection of COPD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Under these conditions, Ze was the most suitable for correctly identifying the effects of COPD, with a sensitivity of 100% and a specificity of 90%. These promising results are consistent with those obtained previously21,44 and suggest that the Zrs observed in different phases of the respiratory cycle may be useful in the detection of COPD.…”
Section: Discussionsupporting
confidence: 92%
“…The resulting signals are recorded by an analog signal processing circuit to perform calculations to obtain the Zrs (Zrs = P/V´') in real time. This variable is known as the impedance module and describes the total mechanical load of the respiratory system, including the effects of resistance and reactance 11,21. The instrument was calibrated by means of a reference mechanical load and, after this, measurement errors were <0.5% 10,11.…”
Section: Methodsmentioning
confidence: 99%
“…The concomitant alteration in autonomic outXow may have implications on the normalcy of parameters of compliance, resistance, and inertance estimated using this method of pulmonary testing. While this pronounced eVect on the modulation of heart rate was observed using forced random ventilation, it is not known if the single sinusoidal method of estimating respiratory impedance has a similar eVect (DuBois et al 1956;Veiga et al 2009) or how the response may be dependent on the frequency of the sinusoid. To our knowledge, this profound eVect of forced oscillation on HRV has not been previously described.…”
Section: Discussionmentioning
confidence: 98%
“…(2) The presence of associated diseases, such as rhinitis (symptoms are present in 90% of cases), gastroesophageal Sleep 5 [16][17][18][19][20] Physiology, exercise, and rehabilitation 12 [21][22][23][24][25][26][27][28][29][30][31][32] COPD 8 [33][34][35][36][37][38][39][40] Pathology 3 [41][42][43] CT 2 [44][45] Occupational medicine 1 46 Pulmonary thromboembolism 2 [47][48] Pulmonary hypertension 3 [49][50][51] Lung cancer 3 [52][53][54] Smoking 2 [55][56] Evaluation of articles on pulmonology published in Brazilian In their study involving patients with severe OSAS, Neves et al found that the use of sildenafil worsens OSAS, as well as causing deleterious cardiovascular effects because of the increased parasympathetic tone and affecting the HR variability. (19) Pires et al, in a study of drivers engaged in night shift work, contradicted the notion that the sleep pattern of older individuals is more negatively affected than that of younger individuals.…”
Section: Asthmamentioning
confidence: 99%
“…Veiga et al used the forced oscillation technique in asthma patients, and this allowed the identification of increased respiratory impedance in such patients. (21) Using the forced oscillation technique, Tramont et al demonstrated that, with ageing, there is a reduction in the homogeneity of the respiratory system, especially in individuals over 70 years of age. (22) Measurement of PEF by five different meters was compared by Takara et al, who observed that there was no agreement among the devices.…”
Section: Asthmamentioning
confidence: 99%